In vivo confocal microscopic findings in patients with limbal stem cell deficiency. Issue 4 (10th February 2012) - Miri, Ammar; Alomar, Thaer; Nubile, Mario; Al-aqaba, Muhamed; Lanzini, Manuela; Fares, Usama; Said, Dalia G; Lowe, James; Dua, Harminder Singh
Abstract : Aim: To describe in vivo confocal microscopy (IVCM) findings in patients with limbal stem cell deficiency (LSCD). Methods: 23 eyes of 17 consecutive patients suffering from LSCD were included in this study. A detailed examination by IVCM was performed in addition to a routine slit-lamp biomicroscopy. Size and density of corneal epithelial and conjunctival epithelial cells on cornea were measured and statistically analysed using SPSS version 8.0 software. Results were compared with histology in select cases. Results: Anatomical and morphological differences were observed between normal corneal cells and conjunctival epithelial cells on cornea. Size and density differences reached statistically significant levels between the normal corneal cells and the conjunctival epithelial cells on cornea (p<0.01). Goblet cells were visible throughout the conjunctivalised corneal epithelium in eight eyes. Several IVCM features could be correlated with histology in six of our patients. Conclusions: A number of features were demonstrated by laser IVCM in patients presenting clinically with LSCD. Some of these features were corroborated with features observed on histological examination of tissue samples.